Preparation method of ecological water permeable brick based on modified sludge

By mixing modified sludge with other materials and using modified sludge as the bonding material during the firing process, the problem of degradation of water permeability during the sludge treatment and permeability brick firing is solved, and high water permeability is achieved It has a permeable brick with flexural strength and meets the requirements of green and environmental protection.

CN119430859AInactive Publication Date: 2025-02-14ZONGYANG COUNTY HENGSHENG NEW BUILDING MATERIALS CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411658612.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-20
Publication Date
2025-02-14
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The existing sludge treatment methods have problems such as environmental pollution, high costs and waste of resources, and the permeable bricks will be degraded during the firing process.

Method used

By mixing the modified sludge with blast furnace slag, quartz sand, feldspar powder and other materials, and using the modified sludge as the bonding material during the firing process, a permeable brick with a high permeability coefficient is formed.

Benefits of technology

It improves the permeability and flexural strength of permeable bricks, realizes the effective utilization of sludge and the recycling of resources, reduces carbon emissions, and conforms to the theme of green and environmental protection.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005142706360000091
    Figure BDA0005142706360000091
Patent Text Reader

Abstract

The invention relates to the technical field of water permeable bricks, and discloses a preparation method of an ecological water permeable brick based on modified sludge, and the preparation method comprises the following steps: (1) obtaining a modifier; (2) mixing a modifier with the sludge, and then carrying out ultraviolet light uniform irradiation treatment to obtain modified sludge; and (3) sequentially mixing the modified sludge, blast furnace slag, quartz sand and feldspar powder together, uniformly mixing, adding into a mold, carrying out compression molding to obtain a green brick, putting the green brick into a box-type resistance furnace, firing, cooling and discharging to obtain the water permeable brick. The water permeable brick prepared by the preparation method disclosed by the invention not only has excellent fracture resistance, but also has a relatively high water permeable coefficient, and the water permeable performance of the water permeable brick can be greatly improved due to the improvement of the water permeable coefficient. The sludge is subjected to a series of modification treatment, and the obtained modified sludge is introduced into the preparation of the water permeable brick as one of the raw materials, so that the performance of the water permeable brick is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of permeable bricks, and in particular to a method for preparing ecological permeable bricks based on modified sludge. Background Art

[0002] A large amount of sewage will be generated in the process of production and life in the city. If the sewage is not treated and discharged directly, it will cause a lot of pollution. Therefore, it is necessary to treat the domestic and production sewage generated by the city so that the water resources used can be recycled. After sewage treatment, a large amount of sludge will be produced. If this large amount of sludge is not treated accordingly or effectively utilized, it will cause secondary pollution to the environment.

[0003] If the sludge is directly piled in the open air, it will emit an unpleasant odor and seriously affect the surrounding air.

[0004] If the sludge is to be landfilled, the existing landfill methods include: paying a fee to the landfill to dispose of it; or digging a pit on the spot for landfilling; both of which require a certain cost, which not only wastes land resources, but also increases costs and reduces economic benefits.

[0005] Permeable bricks are generally bricks used for paving. On the one hand, permeable bricks have good water permeability and air permeability, which can allow rainwater to quickly penetrate into the ground, replenish soil water and groundwater, maintain soil moisture, and improve the living conditions of urban ground plants and soil microorganisms; on the other hand, permeable bricks can absorb moisture and heat, regulate the temperature and humidity of local surface spaces, and play a great role in regulating urban microclimates and alleviating urban heat island effects. The present invention introduces sludge into the preparation of permeable bricks, which not only saves the amount of raw materials for permeable bricks, but also makes rational use of the sludge, which is in line with the current green environmental protection theme.

[0006] Based on this, we proposed a preparation method of ecological permeable bricks based on modified sludge. Summary of the invention

[0007] 1. Technical issues to be resolved

[0008] In view of the deficiencies of the prior art, the present invention provides a method for preparing ecological permeable bricks based on modified sludge.

[0009] (II) Technical solution

[0010] To achieve the above-mentioned purpose, the present invention provides the following technical solutions:

[0011] A method for preparing ecological permeable bricks based on modified sludge comprises the following steps:

[0012] (1) First, zinc nitrate solution and titanium nitrate solution are added to a reaction kettle in sequence, and stirred in a water bath for 40-50 minutes, and then a mixed solution of sodium carbonate and sodium hydroxide is added to adjust the system pH to 10.8, stirred for 4 hours, and then allowed to stand for 20 hours, and then filtered, washed with water until neutral, and dried to obtain a modifier;

[0013] (2) mixing the modifier described in step (1) with the sludge, and then uniformly irradiating the mixture with ultraviolet light for 4-5 hours to obtain modified sludge;

[0014] (3) The modified sludge, blast furnace slag, quartz sand and feldspar powder are mixed together in sequence, and after being mixed evenly, they are added to a mold for pressing to obtain a brick blank, and then the brick blank is placed in a box-type resistance furnace for firing, cooling, and discharging to obtain a permeable brick.

[0015] As a further technical solution, the concentration of the zinc nitrate solution in step (1) is 1.5-2 mol / L;

[0016] The concentration of titanium nitrate solution is 3-4 mol / L;

[0017] The volume ratio of the zinc nitrate solution to the titanium nitrate solution is 1:1.

[0018] As a further technical solution, the mass fraction of sodium carbonate in the mixed solution of sodium carbonate and sodium hydroxide is 10-12%;

[0019] The mass fraction of sodium hydroxide solution is 1%.

[0020] As a further technical solution: the drying in step (1) is carried out in a drying oven;

[0021] The drying temperature was 180°C and the drying time was 1 hour.

[0022] As a further technical solution: in step (2), the mixing ratio of the modifier to the sludge is 3-5g:350g;

[0023] Ultraviolet light with a wavelength of 60nm is used for uniform irradiation treatment.

[0024] As a further technical solution, in step (3), the modified sludge, blast furnace slag, quartz sand and feldspar powder are mixed in a mass ratio of 4-5:10-12:4-6:1-1.5.

[0025] As a further technical solution, the compression molding is:

[0026] First, press and hold the pressure at 8MPa for 30-40s, then increase the pressure to 12MPa and hold the pressure for 10-15s.

[0027] As a further technical solution: during the sintering, the temperature is first increased to 620°C at a heating rate of 6°C / min, kept at that temperature for 45 minutes, and then increased to 1100°C at a heating rate of 10°C / min, kept at that temperature for 2 hours.

[0028] As a further technical solution: when discharging by cooling, the material is cooled to 200° C. before discharging.

[0029] (III) Beneficial effects

[0030] Compared with the prior art, the present invention provides a method for preparing ecological permeable bricks based on modified sludge, which has the following beneficial effects:

[0031] The permeable brick prepared by the present invention not only has excellent flexural resistance, but also has a higher water permeability coefficient. The improvement of the water permeability coefficient can greatly improve the water permeability of the permeable brick.

[0032] The present invention performs a series of modification treatments on the sludge, and introduces the obtained modified sludge as one of the raw materials into the preparation of permeable bricks, thereby improving the performance of the permeable bricks. In the preparation process of the permeable bricks, the brick blanks need to be fired, but the water permeability coefficient of the permeable bricks will be significantly reduced due to the firing. This is because a certain liquid phase will be generated during the firing process, and the liquid phase and the filler will be bonded together, blocking the pores and improving the density of the permeable bricks. Although the mechanical properties are improved, the water permeability is greatly reduced. Therefore, the present invention has made significant improvements on the basis of the existing technology. By using modified sludge as a bonding material, and then in the firing process, due to its strong bonding performance, it can be tightly combined with raw materials such as blast furnace slag and quartz sand, and after firing, capillary-like pores will be generated, which are more evenly distributed and complex, thereby greatly improving the water permeability coefficient of the permeable bricks.

[0033] The present invention introduces blast furnace slag as one of the raw materials for permeable bricks. Blast furnace slag is waste slag discharged when smelting pig iron in a blast furnace, which achieves the purpose of recycling waste resources. The permeable bricks made can help rainwater penetrate into the ground and are applied to the design of urban drainage systems, which is more practical. Using blast furnace slag as one of the raw materials can reduce the carbon emissions of permeable bricks, making them more environmentally friendly. Moreover, it contains rich ingredients such as calcium oxide and silicate. After being combined with modified sludge, it can greatly increase the strength and durability of permeable bricks. Since blast furnace slag has good chemical stability, it can avoid corrosion and other problems of permeable bricks during use. DETAILED DESCRIPTION

[0034] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0035] Example 1

[0036] A method for preparing ecological permeable bricks based on modified sludge comprises the following steps:

[0037] (1) First, zinc nitrate solution and titanium nitrate solution are added to a reaction kettle in sequence, and stirred in a water bath for 40 minutes, and then a mixed solution of sodium carbonate and sodium hydroxide is added to adjust the system pH to 10.8, stirred for 4 hours, and then allowed to stand for 20 hours, and then filtered, washed with water until neutral, and dried to obtain a modifier; the concentration of the zinc nitrate solution is 1.5 mol / L;

[0038] The concentration of titanium nitrate solution is 3 mol / L; the volume ratio of zinc nitrate solution to titanium nitrate solution is 1:1; the mass fraction of sodium carbonate in the mixed solution of sodium carbonate and sodium hydroxide is 10%; the mass fraction of sodium hydroxide solution is 1%. Drying is carried out in a drying oven; the drying temperature is 180°C and the time is 1 hour.

[0039] (2) mixing the modifier and sludge described in step (1) together, and then irradiating the mixture with ultraviolet light for 4 hours to obtain modified sludge; the mixing ratio of the modifier and the sludge is 3 g:350 g;

[0040] Ultraviolet light with a wavelength of 60nm is used for uniform irradiation treatment.

[0041] (3) The modified sludge, blast furnace slag, quartz sand and feldspar powder are mixed together in sequence, and after being mixed evenly, they are added to a mold for pressing and forming to obtain a brick blank, and then the brick blank is placed in a box-type resistance furnace for firing, cooling, and discharging to obtain a permeable brick. The modified sludge, blast furnace slag, quartz sand and feldspar powder are mixed in a mass ratio of 4:10:4:1; the pressing and forming is as follows: first, pressing and holding the pressure at a pressure of 8MPa for 30s, and then increasing the pressure to 12MPa and holding the pressure for 10s; during the sintering, the temperature is first increased to 620℃ at a heating rate of 6℃ / min, and the temperature is kept for 45min, and then the temperature is increased to 1100℃ at a heating rate of 10℃ / min, and the temperature is kept for 2 hours; when cooling and discharging, the temperature is cooled to 200℃ and the material is discharged.

[0042] Example 2

[0043] A method for preparing ecological permeable bricks based on modified sludge comprises the following steps:

[0044] (1) First, zinc nitrate solution and titanium nitrate solution are added to a reaction kettle in sequence, and stirred in a water bath for 45 minutes, and then a mixed solution of sodium carbonate and sodium hydroxide is added to adjust the system pH to 10.8, stirred for 4 hours, and then allowed to stand for 20 hours, and then filtered, washed with water until neutral, and dried to obtain a modifier; the concentration of the zinc nitrate solution is 1.8 mol / L;

[0045] The concentration of titanium nitrate solution is 3.5 mol / L; the volume ratio of zinc nitrate solution to titanium nitrate solution is 1:1; the mass fraction of sodium carbonate in the mixed solution of sodium carbonate and sodium hydroxide is 11%; the mass fraction of sodium hydroxide solution is 1%. Drying is carried out in a drying oven; the drying temperature is 180°C and the time is 1 hour.

[0046] (2) mixing the modifier and sludge described in step (1) together, and then irradiating the mixture with ultraviolet light for 4.5 hours to obtain modified sludge; the mixing ratio of the modifier and the sludge is 4 g:350 g;

[0047] Ultraviolet light with a wavelength of 60nm is used for uniform irradiation treatment.

[0048] (3) The modified sludge, blast furnace slag, quartz sand and feldspar powder are mixed together in sequence, and after being mixed evenly, they are added to the mold for pressing and forming to obtain a brick blank, and then the brick blank is placed in a box-type resistance furnace for firing, cooling, and discharging to obtain a permeable brick. The modified sludge, blast furnace slag, quartz sand and feldspar powder are mixed in a mass ratio of 4.5:11:5:1.2; the pressing and forming is as follows: first, pressing and holding the pressure at a pressure of 8MPa for 32s, and then increasing the pressure to 12MPa and holding the pressure for 12s; during the sintering, the temperature is first raised to 620℃ at a heating rate of 6℃ / min, and the temperature is kept for 45min, and then the temperature is raised to 1100℃ at a heating rate of 10℃ / min, and the temperature is kept for 2 hours; when cooling and discharging, the temperature is cooled to 200℃ and the material is discharged.

[0049] Example 3

[0050] A method for preparing ecological permeable bricks based on modified sludge comprises the following steps:

[0051] (1) First, zinc nitrate solution and titanium nitrate solution are added to a reaction kettle in sequence, and stirred in a water bath for 45 minutes, and then a mixed solution of sodium carbonate and sodium hydroxide is added to adjust the system pH to 10.8, stirred for 4 hours, and then allowed to stand for 20 hours, and then filtered, washed with water until neutral, and dried to obtain a modifier; the concentration of the zinc nitrate solution is 1.6 mol / L;

[0052] The concentration of titanium nitrate solution is 3.8 mol / L; the volume ratio of zinc nitrate solution to titanium nitrate solution is 1:1; the mass fraction of sodium carbonate in the mixed solution of sodium carbonate and sodium hydroxide is 11%; the mass fraction of sodium hydroxide solution is 1%. Drying is carried out in a drying oven; the drying temperature is 180°C and the time is 1 hour.

[0053] (2) mixing the modifier and sludge described in step (1) together, and then irradiating the mixture with ultraviolet light for 4.5 hours to obtain modified sludge; the mixing ratio of the modifier and the sludge is 3.5 g:350 g;

[0054] Ultraviolet light with a wavelength of 60nm is used for uniform irradiation treatment.

[0055] (3) The modified sludge, blast furnace slag, quartz sand and feldspar powder are mixed together in sequence, and after being mixed evenly, they are added to the mold for pressing and forming to obtain a brick blank, and then the brick blank is placed in a box-type resistance furnace for firing, cooling, and discharging to obtain a permeable brick. The modified sludge, blast furnace slag, quartz sand and feldspar powder are mixed in a mass ratio of 4.6:11:5:1.2; the pressing and forming is as follows: first, the pressing and pressure holding treatment is carried out at a pressure of 8MPa for 38s, and then the pressure is increased to 12MPa and the pressure is held for 14s; during the sintering, the temperature is first increased to 620℃ at a heating rate of 6℃ / min, and the temperature is kept for 45min, and then the temperature is increased to 1100℃ at a heating rate of 10℃ / min, and the temperature is kept for 2 hours; when cooling and discharging, the temperature is cooled to 200℃ and the material is discharged.

[0056] Example 4

[0057] A method for preparing ecological permeable bricks based on modified sludge comprises the following steps:

[0058] (1) First, zinc nitrate solution and titanium nitrate solution are added to a reaction kettle in sequence, and stirred in a water bath for 50 minutes, and then a mixed solution of sodium carbonate and sodium hydroxide is added to adjust the system pH to 10.8, stirred for 4 hours, and then allowed to stand for 20 hours, and then filtered, washed with water until neutral, and dried to obtain a modifier; the concentration of the zinc nitrate solution is 2 mol / L;

[0059] The concentration of titanium nitrate solution is 4 mol / L; the volume ratio of zinc nitrate solution to titanium nitrate solution is 1:1; the mass fraction of sodium carbonate in the mixed solution of sodium carbonate and sodium hydroxide is 12%; the mass fraction of sodium hydroxide solution is 1%. Drying is carried out in a drying oven; the drying temperature is 180°C and the time is 1 hour.

[0060] (2) mixing the modifier and sludge described in step (1) together, and then irradiating the mixture with ultraviolet light for 5 hours to obtain modified sludge; the mixing ratio of the modifier and the sludge is 5 g:350 g;

[0061] Ultraviolet light with a wavelength of 60nm is used for uniform irradiation treatment.

[0062] (3) The modified sludge, blast furnace slag, quartz sand and feldspar powder are mixed together in sequence, and after being mixed evenly, they are added to the mold for pressing and forming to obtain a brick blank, and then the brick blank is placed in a box-type resistance furnace for firing, cooling, and discharging to obtain a permeable brick. The modified sludge, blast furnace slag, quartz sand and feldspar powder are mixed in a mass ratio of 5:12:6:1.5; the pressing and forming is as follows: first, pressing and holding the pressure at a pressure of 8MPa for 40s, and then increasing the pressure to 12MPa and holding the pressure for 15s; during the sintering, the temperature is first increased to 620℃ at a heating rate of 6℃ / min, and the temperature is kept for 45min, and then the temperature is increased to 1100℃ at a heating rate of 10℃ / min, and the temperature is kept for 2 hours; when cooling and discharging, the temperature is cooled to 200℃ and the material is discharged.

[0063] Comparative Example 1

[0064] A method for preparing ecological permeable bricks based on modified sludge comprises the following steps:

[0065] (1) Sludge, blast furnace slag, quartz sand and feldspar powder are mixed together in sequence, mixed evenly, added to a mold for pressing and forming to obtain a brick blank, and then the brick blank is placed in a box-type resistance furnace for firing, cooling, and discharging to obtain a permeable brick. Sludge, blast furnace slag, quartz sand and feldspar powder are mixed in a mass ratio of 4:10:4:1; pressing and forming are as follows: first pressing and holding pressure treatment at a pressure of 8MPa for 30s, then increasing the pressure to 12MPa and holding the pressure for 10s; during the sintering, first heating to 620℃ at a heating rate of 6℃ / min, holding the temperature for 45min, then heating to 1100℃ at a heating rate of 10℃ / min, holding the temperature for 2 hours; when cooling and discharging, cool to 200℃ and discharge.

[0066] test

[0067] Mold size: 50mm×25mm×15mm;

[0068] The flexural strength of the examples and comparative examples was tested according to the standard of "Permeable Pavement Bricks and Permeable Pavement Panels";

[0069] Table 1

[0070] Flexural strength MPa Example 1 11.3 Example 2 11.8 Example 3 12.5 Example 4 11.4 Comparative Example 1 8.1

[0071] It can be seen from Table 1 that the permeable bricks prepared by the present invention have higher flexural strength.

[0072] The mold size is 50mm×25mm×15mm. The water permeability coefficient (GB / T25993—2010) of the permeable bricks of the embodiment and the comparative example is tested:

[0073] Table 2

[0074]

[0075]

[0076] It can be seen from Table 2 that the permeable bricks prepared by the present invention have a higher water permeability coefficient. Although the embodiments of the present invention have been shown and described, it is understood by those skilled in the art that various changes, modifications, substitutions and variations can be made to these embodiments without departing from the principles and spirit of the present invention, and the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A method for preparing ecological permeable bricks based on modified sludge, characterized in that: The following steps are involved: (1) First, zinc nitrate solution and titanium nitrate solution are added to a reaction kettle in sequence, and stirred in a water bath for 40-50 minutes, and then a mixed solution of sodium carbonate and sodium hydroxide is added to adjust the system pH to 10.8, stirred for 4 hours, and then allowed to stand for 20 hours, and then filtered, washed with water until neutral, and dried to obtain a modifier; (2) mixing the modifier described in step (1) with the sludge, and then uniformly irradiating the mixture with ultraviolet light for 4-5 hours to obtain modified sludge; (3) The modified sludge, blast furnace slag, quartz sand and feldspar powder are mixed together in sequence, and after being mixed evenly, they are added to a mold for pressing to obtain a brick blank, and then the brick blank is placed in a box-type resistance furnace for firing, cooling, and discharging to obtain a permeable brick.

2. The method for preparing an ecological permeable brick based on modified sludge according to claim 1, characterized in that: The concentration of the zinc nitrate solution in step (1) is 1.5-2 mol / L; The concentration of titanium nitrate solution is 3-4 mol / L; The volume ratio of the zinc nitrate solution to the titanium nitrate solution is 1:

1.

3. The method for preparing an ecological permeable brick based on modified sludge according to claim 2, characterized in that: The mass fraction of sodium carbonate in the mixed solution of sodium carbonate and sodium hydroxide is 10-12%; The mass fraction of sodium hydroxide solution is 1%.

4. The method for preparing an ecological permeable brick based on modified sludge according to claim 2, characterized in that: The drying in step (1) is carried out in a drying oven; The drying temperature was 180°C and the drying time was 1 hour.

5. The method for preparing an ecological permeable brick based on modified sludge according to claim 1, characterized in that: In step (2), the mixing ratio of the modifier to the sludge is 3-5 g:350 g; Ultraviolet light with a wavelength of 60nm is used for uniform irradiation treatment.

6. The method for preparing an ecological permeable brick based on modified sludge according to claim 1, characterized in that: In step (3), the modified sludge, blast furnace slag, quartz sand and feldspar powder are mixed in a mass ratio of 4-5:10-12:4-6:1-1.

5.

7. The method for preparing ecological permeable bricks based on modified sludge according to claim 6, characterized in that: The compression molding is as follows: First, press and hold the pressure at 8MPa for 30-40s, then increase the pressure to 12MPa and hold the pressure for 10-15s.

8. The method for preparing an ecological permeable brick based on modified sludge according to claim 1, characterized in that: During the sintering, the temperature is first increased to 620° C. at a heating rate of 6° C. / min and kept at that temperature for 45 minutes, and then increased to 1100° C. at a heating rate of 10° C. / min and kept at that temperature for 2 hours.

9. The method for preparing an ecological permeable brick based on modified sludge according to claim 1, characterized in that: During the cooling and discharging, the material is cooled to 200° C. and then discharged.